2022
DOI: 10.18502/ijph.v51i7.10085
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Syphilis Infections among the Iranian Population: A Systematic Review and Meta-Analysis

Abstract: Background: Syphilis is one of the most important sexually transmitted infections (STI) and a public health problem, but the literature describing the true burden of syphilis is limited. In Iran, there are no accurate results on the prevalence of syphilis. This study aimed to conduct a systematic review and meta-analysis of syphilis in Iran. Methods: Following PRISMA guidelines, we conducted a systematic review and meta-analysis of studies published on the prevalence of Syphilis in Iran. We systematicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The epidemiology of Syphilis is reported differently but approximately, annually 100,000 individuals die from syphilis while 12 million cases are reported yearly. Only 0.05% of the blood donors found to have syphilis 3 . About 0.51% of blood donors from Thalassery India are diagnosed through ELISA that they were infected by Treponema pallidum 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The epidemiology of Syphilis is reported differently but approximately, annually 100,000 individuals die from syphilis while 12 million cases are reported yearly. Only 0.05% of the blood donors found to have syphilis 3 . About 0.51% of blood donors from Thalassery India are diagnosed through ELISA that they were infected by Treponema pallidum 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the number of HIV-infected individuals who succumbed to mortality due to any cause reached 15,845 by the end of 2018 [ 6 ]. Additionally, in the year 2018, a report from Iran revealed that out of a total of 1,080 patients, 155 individuals (14.3%) were diagnosed with C. trachomatis infection [ 7 ]. In 2022, the prevalence of combined syphilis in Iran was recorded to be 0.1%, with a prevalence rate of 0.4% in males and 0.6% in females.…”
Section: Introductionmentioning
confidence: 99%
“…Syphilis rates among pregnant women vary regionally: 6.5% in Southern Africa, 4.6% in East Africa, and 4.0% in West Africa [ 6 ]. In 2020, Iran had a 0.1% syphilis prevalence, encompassing primary and secondary cases [ 7 ]. In 2019, syphilis diagnosis rate in South China was 112 per 100,000 for older individuals and 48.1 per 100,000 for younger individuals, indicating a significant age-related difference [ 8 ].…”
Section: Introductionmentioning
confidence: 99%